2011
DOI: 10.1186/1472-6939-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Be known, be available, be mutual: a qualitative ethical analysis of social values in rural palliative care

Abstract: BackgroundAlthough attention to healthcare ethics in rural areas has increased, specific focus on rural palliative care is still largely under-studied and under-theorized. The purpose of this study was to gain a deeper understanding of the values informing good palliative care from rural individuals' perspectives.MethodsWe conducted a qualitative ethnographic study in four rural communities in Western Canada. Each community had a population of 10, 000 or less and was located at least a three hour travelling di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 40 publications
(55 reference statements)
1
50
0
Order By: Relevance
“…Building upon inherent capacity is particularly important for ensuring that programs are embedded within the community and less vulnerable to the rapid cycles of change that are typical of modern healthcare. Previous research has illustrated how healthcare restructuring can have negative unintended consequences on palliative care capacity in rural communities 16,24…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Building upon inherent capacity is particularly important for ensuring that programs are embedded within the community and less vulnerable to the rapid cycles of change that are typical of modern healthcare. Previous research has illustrated how healthcare restructuring can have negative unintended consequences on palliative care capacity in rural communities 16,24…”
Section: Resultsmentioning
confidence: 99%
“…Rural care, based upon a generalist model, is ideally suited to such an approach. The high degree of connection between providers in rural communities has the potential to support person- and family-centered care 15,16,19. However, previous studies have indicated that challenges occur around providing 24/7 access and thus symptoms may not be treated in a timely manner.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations